A collision avoidance approach via negotiation protocol for a swarm of USVs. (15th March 2021) - Ma, Yong; Zhao, Yujiao; Incecik, Atilla; Yan, Xinping; Wang, Yulong; Li, Zhixiong
Abstract: For solving collision avoidance issue of a swarm of unmanned surface vehicles (USVs) under complex situations, a collision avoidance approach using a negotiation protocol for USVs is proposed. To fulfill the collision avoidance, we first discuss the maneuverability, encounter situation division. Then, a collision avoidance ad-hoc network is constructed for the negotiation communication between USVs. Moreover, to cope with complex collision avoidance situations, an USV negotiation protocol is designed. Simulations under generous complex scenarios are carried out to validate the effectiveness of our approach. Results verify that our approach is effective and reliable for resolving the problem of a swarm of USVs collision avoidance. Highlights: A new collision avoidance is proposed for a swarm of USVs. A negotiation protocol is developed for the collision avoidance. Numerical evaluation result demonstrates good collision avoidance.